Advancing feminist innovation in sport studies: A transdisciplinary dialogue on gender, health and wellbeing - Holly Thorpe; Sheree Bekker; Simone Fullagar; Nonhlanhla Mkumbuzi; Sophia Nimphius; Madeleine Pape; Stacy T. Sims; A. Travers (Frontiers Media, 2023)
Athlete health and wellbeing requires a holistic, multidimensional approach to understanding, supporting, and treating individual athletes. Building more supportive, inclusive, and equitable environments for the health and wellbeing of women and gender expansive people further requires gender-responsive approaches that promote broader cultural change. Feminist sport and exercise medicine practitioners, sports scientists, and social science researchers are increasingly coming together in their efforts to do this work. However, working across disciplines inevitably includes an array of ontological, epistemological, and political challenges. In this paper, we offer a curated ‘dialogue’ with a group of feminist scholars engaged in research and practice across disciplines, bringing them together to discuss some of the most pressing gendered issues in sport today (i.e., ACL injury, concussion, menstruation in sport, mental health, gender categories). In so doing, we amplify the voices of those working (empirically and clinically) at the disciplinary intersections of gender, sport and health, and learn about some of the current and future possibilities for transdisciplinary innovations and strategies for building (responsiveness to) cultural change.